A corpus-based analysis of the Swedish passive alternation. Issue 2 (16th October 2014) - De Cuypere, Ludovic; Baten, Kristof; Rawoens, Gudrun; Andersen, Gisle; Hardt, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> This article presents a corpus-based investigation of the motivations behind the use of the s-passive and the bli-passive in contemporary written Swedish. Following a probabilistic approach to language variation and building on observations in the literature, we examine the simultaneous effects of semantic and syntactic factors by means of a multivariate statistical analysis. Our corpus sample includes 1, 197 passive sentences of three Swedish verbs, which alternate in their use of the passive (acceptera 'accept', behandla 'treat' and välja 'choose'). The results suggest that the choice of passive form is significantly associated with five predictor variables: Subject Animacy, Subject Number, Modal Verb, Av-phrase ('by'-phrase) and Aktionsart. Among these, Subject Animacy and Modal Verb appear to yield the strongest impact effect on the choice of passive form. The study adds to earlier research in that it allows for a more accurate analysis of the simultaneous effect and relative strength of each factor on the speaker's choice of one of the passive forms.